The Influence of Live Streaming Features and Online Customer Reviews on Purchasing Decisions through Trust as A Mediating Variable - Firdausy, Salsa Bila Kusuma; Padmantyo, Sri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research seeks to establish the impact of the live streaming feature and online customer reviews on the purchasing decisions with trust as the mediating variable in the Shopee e-commerce platform. Methodology: Based on a quantitative research paradigm, a survey was administered to 215 Shopee active users in the Solo Raya who had engaged in live streaming show. The responses were analyzed using the SmartPLS 3 analysis tool, which aids in structural equation modeling to understand the relation between research variables. Results: The studies indicated that discount vouchers and online customer reviews influence the level of trust and purchase decision significantly whereas Live selling did not give a significant result. The results also indicated that Trust alternatively fully mediated the influence of discount voucher on the purchase decision concerning online customer review. Application/Originality/Value: The results of this study contribute to the understanding of consumer trust, specifically in the LSEe context, as it identifies the role of the discount strategy and the management of customer reviews in comparison to the direct impact of the live selling itself.